Silicon nitride waveguides with directly grown WS2 for efficient second-harmonic generation. Issue 1 (1st December 2021) - Liu, Ning; Yang, Xi; Zhu, Zhihong; Chen, Feng; Zhou, Yangbo; Xu, Jipeng; Liu, Ken
Abstract : Direct growth of large-area homogeneous monolayer WS2 onto Si3 N4 waveguides is demonstrated and the waveguides show obvious second-harmonic generation. The work is an important step toward on-chip integration of 2D materials with Si3 N4 photonics. Abstract : Different functions can be directly realized by silicon (Si) in integrated electronic circuits. Although Si and silicon nitride (Si3 N4 ) photonics have shown great potential in integrated optoelectronic devices, different functions, such as light generation, transparency for guided light, and light detection, cannot be simultaneously achieved only by Si or Si3 N4 . Second-order nonlinearity is another optical property they do not possess due to their centrosymmetric properties. Several kinds of 2D materials emerged recently and were transferred to specified photonic devices aimed at improving their nonlinear performance. However, the transferring methods are time-consuming, unable to achieve large-scale production, and will inevitably cause materials damage and introduce impurities at the interface. Herein, we demonstrate the direct growth of large-area homogeneous monolayer WS2 via a physical vapor deposition method onto Si3 N4 waveguides. The WS2 growth can be controlled mainly along the Si3 N4 waveguides and the waveguides show an obvious enhancement of second-harmonic generation with the elongated WS2 coverage. The direct growth of WS2 endows Si3 N4 integrated photonics with new nonlinear optical properties. As an alternative method of transferring 2D materials, the method we present here is compatible with large-scale integrated photonic fabrication, which lays the foundation for on-chip integrated optical fabrication and applications.